2015
DOI: 10.1523/jneurosci.0496-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide Modulation of Heteromeric Kv1 Channels Adjusts Output of Spiral Ganglion Neurons from Hearing Mice

Abstract: Spiral ganglion neurons (SGNs) relay acoustic code from cochlear hair cells to the brainstem, and their stimulation enables electrical hearing via cochlear implants. Rapid adaptation, a mechanism that preserves temporal precision, and a prominent feature of auditory neurons, is regulated via dendrotoxin-sensitive low-threshold voltage-activated (LVA) K ϩ channels. Here, we investigated the molecular physiology of LVA currents in SGNs cultured from mice following the onset of hearing (postnatal days 12-21). Kv1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 59 publications
6
53
0
Order By: Relevance
“…A number of earlier studies have reported a significant increase in firing output following application of dendrotoxin, increasing the firing rate of both rapidly-adapting and slowly-adapting neurons in its presence37394142. That result implicated K V 1.1 and K V 1.2 in the control of firing frequency.…”
Section: Discussionmentioning
confidence: 89%
“…A number of earlier studies have reported a significant increase in firing output following application of dendrotoxin, increasing the firing rate of both rapidly-adapting and slowly-adapting neurons in its presence37394142. That result implicated K V 1.1 and K V 1.2 in the control of firing frequency.…”
Section: Discussionmentioning
confidence: 89%
“…Based on this, one could speculate that ramped pulses excite sites on the auditory nerve fiber distinct from rectangular pulses to produce steeper growth function. Interestingly, immunostainings show that Kv.1.1and Kv1.2 subunits of the ramp-sensitive KLT channels localize to SGN somata 7 , but whether there is a relation between ramped stimulation, KLT localization and site of excitation has yet to be determined. Indeed, it would be interesting to explore how and at which site ramped and rectangular pulses excite the auditory nerve fibers, using latency data from single-or multiunit neuronal recordings.…”
Section: Discussionmentioning
confidence: 99%
“…First, ramped pulses reportedly match ion channel dynamics of SGN better 4 . SGNs, among other neurons in the auditory system, express low-threshold potassium channels (KLT) 7 . These ion channels are sensitive to the rate of change of a synaptic input current and regulate firing patterns, in particular adaptation to high stimulation rate, by extending the refractory period and a sharp timing of the action potential [7][8][9][10][11] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We blocked these steps with three chemical tools: neomycin and an anti-PIP 2 antibody, which block the access of PLC to PIP 2 ; and the non-hydrolysable PIP 2 analogue diC8-PIP 2 , a putative competitive inhibitor of phospholipases [25][26][27][28]. The presence of each of the inhibitors prevented the PE-induced shift in I hERG activation half voltage (Fig.…”
Section: Intracellular Pathway Mediating the α1-ar Modulation Of Hergmentioning
confidence: 99%